Antihuman epidermal growth factor receptor 2 antibody herceptin inhibits autocrine motility factor (AMF) expression and potentiates antitumor effects of AMF inhibitors. - Talukder, A; Bagheri-Yarmand, R; Williams, R; Ragoussis, J; Kumar, R; Raz, A (2002)
Overexpression of the human epidermal growth factor receptor (HER) 2 has been linked to the development and maintenance of malignant phenotypes in breast tumors. In addition, the growth and dissemination of human cancers are regulated in part by the autocrine motility factor (AMF)/phosphoglucose isomerase shown to be up-regulated by heregulin (HRG) in breast cancer cells. This study was undertaken to explore the effect of anti-HER2 monoclonal antibody 4D5 [Herceptin (HCT)] on AMF expression and the potential of its augmentation by specific simple sugar AMF inhibitors. Here we show that HCT treatment of high HER2-expressing breast cancer SK-BR3, BT-474, and ZR-75R cells resulted in down-regulation of AMF mRNA and protein. HCT inhibited the ability of HRG to induce AMF expression in cells with a normal HER2 level, and HCT-mediated down-regulation could be reversed by HRG treatment in breast cancer cells with a high HER2 level. HCT also inhibited transcription from a chimeric pGL3-Luc vector-based reporter system containing the 1.8-kb promoter region of human AMF. Treatment of breast cancer cells with the combination of HCT and specific AMF inhibitors, erythrose 4-phosphate or D-mannose 6-phosphate, resulted in an additive inhibitory effect on both the growth rate and invasiveness of cells as compared with treatment with each agent alone. Results presented here suggest that HCT can effectively block both ligand-induced and constitutive expression of AMF associated with high HER2 overexpression, implying a role of the AMF pathway in the action of HCT. Accordingly, the combination of AMF inhibitor with HCT can potentiate the growth-inhibitory and anti-invasive action of HCT in breast cancer cells.